(untitled) (Revista Innova Educación, 2020)
This article reflects on connectivism as a pedagogical approach for the development of learning processes that can be generated from information and communication technologies applied to education. It is presented as a pedagogical alternative that has gone through a series of epistemological debates about its theoretical character and pedagogical value to transform traditional educational practices. The methodology used was the documentary review and includes the main investigations on connectivism that have been carried out in Latin American countries, the United States and Spain, among others, and which are referenced in various databases, such as Redalyc, Dialnet, Springer and Scopus. In the results, the different theoretical and conceptual discussions about connectivism are presented, emphasizing the contributions that it has had to the consolidation of new pedagogical and educational currents for the development of learning processes.